2012
DOI: 10.1016/j.jrtpm.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Trip plan generation using optimization: A benchmark of freight routing and scheduling policies within the carload service segment

Abstract: The rail freight carload service segment enables the distribution of freight volumes down to the unit of single rail cars, and stand as an important alternative to road transportation. However, this service segment is often associated with significant uncertainties and variations in daily freight volumes. Such uncertainties are challenging to manage since operating plans generally are established long in advance of operations. Flexibility can instead be found in the way trip plans are generated. Previous resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…They assigned the boxes to train wagons, assuming that train timetables are fixed and boxes can be transported by more than one train. Backåker et al [24] suggested an optimisation-based freight routing and scheduling policy to generate trip plans for railcars restricted by customer commitments. Qu et al [25] developed a formulation to simulate the transportation process of railcars when a station in the railroad network is congested caused by an emergency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They assigned the boxes to train wagons, assuming that train timetables are fixed and boxes can be transported by more than one train. Backåker et al [24] suggested an optimisation-based freight routing and scheduling policy to generate trip plans for railcars restricted by customer commitments. Qu et al [25] developed a formulation to simulate the transportation process of railcars when a station in the railroad network is congested caused by an emergency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, railway risk management based on fuzzy reasoning and fuzzy hierarchical analysis method to process railway risk information also provides support to assist railway safety risk decision-making [11][12][13]. Recent studies [14][15][16][17][18] on railway freight transportation route decision-making, for example, optimized freight routing and scheduling strategies, have been developed and applied to solve the problems in railway freight planning [19]. The hub-and-spoke technique [20] and the real-time scheduling and routing method in the railway network [21] also provide a basis for the solutions of ROF-TRD [22,23].…”
Section: Introductionmentioning
confidence: 99%